Use of plant growth regulators in fig tree seedlings ‘Roxo de Valinhos’ - Souza, Jackson Mirellys Azevêdo [UNESP]; Leonel, Sarita [UNESP]; Silva, Marcelo de Souza [UNESP]; Ferreira, Rafael Bibiano [UNESP]; Ferraz, Rafael Augusto; Modesto, Joyce Helena [UNESP]; Tecchio, Marco Antonio [UNESP] (My University, 2019)
The application of plant growth regulators can promote better development of the seedlings, essential for the success of fruit growing. The current study aims to evaluate the use of plant growth regulators in fig tree seedlings ‘Roxo de Valinhos’. The experiment was carried out in a suspended nursery covered with plastic, using rooted cuttings of the cultivar Roxo de Valinhos. Four applications were made with a commercial product, known as Stimulate®, at doses of 0, 50, 100, 150, and 200 mL L -1 . Using a randomized block experimental design, the study was subdivided into plots (doses X days of the last application [after 0, 7, 14 and 21]). The following traits were evaluated: stem and root length; stem diameter; root volume; leaf number; leaf area; stem, leaf and root dry mass; specific leaf area, leaf weight ratio; leaf area ratio; and chlorophyll total. Results indicated that the product promoted greater seedlings development at a dose range from 100 to 150 mL L -1 . Different dose levels did not vary according to the days after product application. Furthermore, using such technique enabled seedlings of higher quality and vigour.
Uso de reguladores vegetais em mudas de figueira ‘Roxo de Valinhos’
Keywords: Auxin; Cytokinin; Ficus carica; Giberelin; Propagation